Inflation Targeting and Interest Rate Dynamics in the Euro - Petkova, Anika (Research Papers, 2024)
Inflation targeting is a key component of monetary policy for most countries around the world, as the main task of central banks is the pursuit of price stability. Maintaining a certain target rate of inflation turns out to be a difficult task in the conditions of numerous external shocks and the relatively quick transition from unconventional to conventional monetary policy. The European Central Bank, as well as the Fed and other central banks, initiate increases in their key interest rates in response to resource price dynamics in global markets. The observed rise in the general price level has its impact on interest rates, which is projected on macroeconomic activity, incl. the level of domestic investment, household consumption, real GDP and other key variables.
Keywords: Monetary policy; Inflation targeting; Economic shock; Interest rates; Real GDP; ECB; FED; Euro area